2015
DOI: 10.1177/0886260515589928
|View full text |Cite
|
Sign up to set email alerts
|

Secure Attachment Moderates the Relation of Sexual Trauma With Trauma Symptoms Among Adolescents From an Inpatient Psychiatric Facility

Abstract: Experiencing sexual trauma has been linked to internalizing and externalizing psychopathologies. Insecure attachment has been shown to moderate the relation between sexual trauma and trauma symptoms among adults. However, few studies have explored relations among sexual trauma, attachment insecurity, and trauma symptoms in adolescence, and none have used developmentally appropriate measures. The present study sought to examine attachment security as a potential moderator of the relation between having a histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
2
22
1
Order By: Relevance
“…They were able to have distinct representations of the different parenting received from their birth and foster parents (Ahmed et al, 2015), although they maintained insecure state of mind regarding attachment toward their biological parents (Joseph et al, 2014). A further study (Jardin et al, 2015) found that attachment security shielded adolescents who experienced sexual trauma against the later occurrence of trauma symptoms.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…They were able to have distinct representations of the different parenting received from their birth and foster parents (Ahmed et al, 2015), although they maintained insecure state of mind regarding attachment toward their biological parents (Joseph et al, 2014). A further study (Jardin et al, 2015) found that attachment security shielded adolescents who experienced sexual trauma against the later occurrence of trauma symptoms.…”
Section: Resultsmentioning
confidence: 97%
“…Security attachment was also found to be a protective factor against the onset of depression in the children of depressed mothers because of the ability of secure children to regulate emotions as well as to adopt successful coping strategies throughout periods of stress (Fox and Borelli, 2015). In general, a prevalence of insecurely attached children was found in clinical samples (Target et al, 2003; Shmueli-Goetz et al, 2008; Venta et al, 2014; Bizzi et al, 2015; Glazebrook et al, 2015; Jardin et al, 2015). Disorganized attachment was associated with child experiences of depressive symptoms and shyness, and with parent-reports of social anxiety, inattention, and thought problems (Borelli et al, 2010b) as well as with disruptive behavior and Somatic Symptoms Disorders (SSDs; Bizzi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…One study to date examined the associations between attachment insecurity within a sample of preschoolers who had been exposed to CSA, finding that within this population, insecurity conferred risk for internalizing and externalizing difficulties (Zéphyr et al, 2015). To our knowledge, only a single study has tested the contributions of both CSA and attachment to youth's psychological adjustment; Jardin et al found that among adolescents receiving inpatient psychiatric care, attachment security moderates the association between CSA and trauma symptoms (Jardin, Venta, Newlin, Ibarra, & Sharp, 2015), such that adolescents with insecure attachment and CSA exposure showed significantly greater trauma symptoms.…”
Section: Attachment Sexual Abuse and Psychopathologymentioning
confidence: 99%
“…The rather strong association between AR avoidance and posttraumatic avoidance may imply, on the one hand, that attachment insecurities lead to an increase in posttraumatic avoidance, and, on the other, that posttraumatic avoidance leads to attachment insecurities in close relationships. The comparison of our results with existing research is difficult, as most of the studies included adults and comparable adolescents studies used different assessment methods and did not report dimensional attachment scores [21][22][23][24]. One comparable study might be the work of Lim et al [25] that used the ECR-R in a sample of college undergraduates with various traumatic events.…”
Section: Results On the Association Between Attachment And Trauma Symmentioning
confidence: 81%
“…However, studies that focus on adolescents' and young adults' attachment and its association with PTSS are sparse and show mixed results. Using a categorical approach, some studies reported a relationship between attachment status and PTSS in the expected direction [21][22][23], whereas another failed to prove this association [24]. To our knowledge, there is only one paper by Lim et al [25] that analyzed attachment dimensions and their association with PTSS in young people.…”
Section: Attachment Trauma and Posttraumatic Stress Symptomsmentioning
confidence: 99%